-x-4=4x+6

Simple and best practice solution for -x-4=4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-4=4x+6 equation:


Simplifying
-1x + -4 = 4x + 6

Reorder the terms:
-4 + -1x = 4x + 6

Reorder the terms:
-4 + -1x = 6 + 4x

Solving
-4 + -1x = 6 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-4 + -1x + -4x = 6 + 4x + -4x

Combine like terms: -1x + -4x = -5x
-4 + -5x = 6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-4 + -5x = 6 + 0
-4 + -5x = 6

Add '4' to each side of the equation.
-4 + 4 + -5x = 6 + 4

Combine like terms: -4 + 4 = 0
0 + -5x = 6 + 4
-5x = 6 + 4

Combine like terms: 6 + 4 = 10
-5x = 10

Divide each side by '-5'.
x = -2

Simplifying
x = -2

See similar equations:

| -3-11=6y+16 | | 7x+8x-6= | | 5-8(7-n)=-91 | | 4+(-12)+23+(-8)= | | 136+38x=x+163 | | 2x-138=-7x+114 | | 15u-17u-(-20)=-6 | | 9x(-4)+3y-x+y-(-2)= | | 3x+1+6x=-89 | | 38x+136=x+163 | | 6x+5-5x=10 | | 5t=3(7t) | | -10-2x=6x+2(-7x+7) | | -8+7x+3x=-8 | | x+5-2x= | | Y=100-4n | | -7r+6t-8s-5r+12s+4t-t+2s-11r= | | 3c-3=6 | | -25=a(x-3)+3 | | 12-4x=3x^3-x^2 | | 8x-9x^3+1=0 | | .005x-.07=.02x+.0032 | | 18x^2+21x-49=0 | | 5=2+3s | | 5n+17=8(-8-3n)-6 | | 9-0.1k=9 | | 2-5v=-v+2(1+7v) | | x+5+2x= | | 12-7n=6-8n | | 3(2x+3)=2x+21 | | 59x-(21x+34)=0 | | 28-5n=3(5-8n)-6 |

Equations solver categories